Basis of bone metabolism around dental implants during osseointegration and peri‐implant bone loss - Insua, Angel; Monje, Alberto; Wang, Hom‐Lay; Miron, Richard J. (Journal of biomedical materials research. Part A, 2017)
Despite the growing number of publications in the field of implant dentistry, there are limited studies to date investigating the biology and metabolism of bone healing around dental implants and their implications in peri‐implant marginal bone loss. The aim of this review article is to provide a thorough understanding of the biological events taking place during osseointegration and the subsequent early and late phases of bone remodeling around dental implants. An update on the coupling mechanism occurring during bone resorption‐bone remodeling is provided, focused on the relevance of the osteocytes, bone lining cells and immune cells during bone maintenance. An electronic and manual literature search was conducted by three independent reviewers in several databases, including MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and Cochrane Oral Health Group Trials Register databases for articles up to September 2016 with no language restriction. Local bone metabolism is subject to signals from systemic calcium‐phosphate homeostasis and bone remodeling. Three areas of interest were reviewed due to recent reported compromises in bone healing including the putative effects of (1) cholesterol, (2) hyperlipidemia, and (3) low vitamin D intake. Moreover, the prominent influence of osteocytes and immune cells is discussed as being key regulators during dental implant osseointegration and maintenance. These cells are of crucial importance in the presence of biofilm accumulation and their associated byproducts that leads to hard and soft tissue breakdown; the so called peri‐implantitis. Factors that could negatively impact osteoclastogenesis or osteal macrophage activation should be monitored in future research including implant placement/torque protocols, bone characteristics, as well as meticulous maintenance programs to favor osseointegration and future long‐term stability and success of dental implants. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 2075–2089, 2017.